2021
DOI: 10.7759/cureus.20746
|View full text |Cite
|
Sign up to set email alerts
|

Why Pulmonary Vasodilation May Be Part of a Key Strategy to Improve Survival in COVID-19

Abstract: Oxygenation is a function of both ventilation and perfusion. While approaches to the treatment of COVID-19 have focused largely on ventilation strategies and antiviral therapies, attention towards the improvement of vascular perfusion defects has been neglected. This article examines clinical findings that indicate perfusion defects are a critical component of COVID-19 pathophysiology. They also support the notion that medications that promote perfusion with pulmonary vasodilatation can yield significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Several authors, considering: (1) the importance of intracellular calcium for the life cycle of viruses, (2) the positive association between hypocalcemia with COVID-19 severity; (3) the importance of promoting perfusion with pulmonary vasodilatation, have suggested an interest in calcium channel blockers (CCBs) for the treatment of people infected with COVID-19 [ 2 , 3 , 4 ]. To satisfy their need for calcium, several viruses induce an increased flux of calcium across cell membranes: CCBs reduce the levels of intracellular calcium [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors, considering: (1) the importance of intracellular calcium for the life cycle of viruses, (2) the positive association between hypocalcemia with COVID-19 severity; (3) the importance of promoting perfusion with pulmonary vasodilatation, have suggested an interest in calcium channel blockers (CCBs) for the treatment of people infected with COVID-19 [ 2 , 3 , 4 ]. To satisfy their need for calcium, several viruses induce an increased flux of calcium across cell membranes: CCBs reduce the levels of intracellular calcium [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Le Corre and Loas have summarized most of the information about in silico, in vitro, and in vivo studies specifically for different FIASMAs in their reviews 23,30 . Of potential therapeutic significance, calcium channel blockers (CCB) have been reported to decrease the risk of death by COVID‐19 18,31–36 . Although CCB are usually prescribed for hypertension treatment (e.g., amlodipine), they can also cause pulmonary vasodilatation.…”
Section: Fiasmasmentioning
confidence: 99%
“…Although CCB are usually prescribed for hypertension treatment (e.g., amlodipine), they can also cause pulmonary vasodilatation. Of therapeutic significance, pulmonary vasodilators can have beneficial effects in moderate or severe COVID‐19 infection by increasing the oxygenation of the lung cells 35,37,38 . As we will discuss in the following sections, amlodipine is a characteristic FIASMA, 29 and can also inhibit SARS‐CoV‐2 replication by different mechanisms.…”
Section: Fiasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, taking into account that hypoxia could be a strong factor in COVID-19 progression, the use of fluvoxamine in the early phase of COVID-19 has been suggested in order to counteract some early posthypoxic events ( Grieb et al, 2021 ; Grieb and Rejdak, 2021 ; Rejdak and Grieb, 2021 ). Additionally, retrospective observational studies have shown that calcium channel blockers (particularly amlodipine that is a FIASMA) promoting pulmonary vasodilatation, have improved clinical outcomes ( Solaimanzadeh 2021 ).…”
Section: Current Evidence On Selective Serotonin Reuptake Inhibitors ...mentioning
confidence: 99%